Adaptive farming to reduce risk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A researcher from an international crop research institute in Nairobi explains how new crop varieties are helping farmers to adapt what they plant to suit variable rainfall patterns.